Pengaruh Interaksi Teman Sebaya Terhadap Kerjasama Anak Usia Dini di Tk Ar-Rayan Lantongau Kecamatan Mawasangka Tengah - Wa Ode Riska Fauzia Ali (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
The aim of this research is to determine and analyze the influence of peer interaction on early childhood collaboration in the Ar-Rayan Lantongau Kindergarten, Katukobari Village. This research is quantitative research with a type of correlational research, namely research that looks for relationships between variables. The population in this study was all Group B students at Ar-Rayan Lantongau Kindergarten, Katukobari Village, totaling 40 students, all of whom were samples in this study. The research instruments used to collect data were questionnaires and documentation. The results obtained in this study showed that peer interaction had a significant influence on early childhood cooperation in the Ar-Rayan Lantongau Kindergarten, Katukobari Village.